The Prevalence of Hyperpalatable Baby Foods and Exposure During Infancy: A Preliminary Investigation - Kong, Kai Ling; Fazzino, Tera L.; Rohde, Kaitlyn M.; Morris, Katherine S. (Frontiers in Psychology, 2021)
Objective: To characterize the prevalence of hyperpalatable foods (HPF) among baby foods in the U.S. and examine the prevalence of HPF exposure and consumption from both baby food and adult food sources among infants aged 9–15 months. Methods: A U.S. baby food database as well as baby foods from three 24-h dietary recalls of 147 infants were used to identify baby foods as HPF per previous publication. HPF exposure was defined as intake of any HPF during the 3-day measurement period. To determine the extent of HFP consumption, % kilocalorie (kcal) intake from HPF was characterized. Results: Only 12% of baby foods were HPF; however, nearly all participants (>90%) consumed HPF, primarily through exposure to adult foods. Younger infants (<12 months) consumed 38% [standard deviation (SD) = 23.6%] of their daily food kcal from HPF and older infants (≥12 months) consumed 52% (SD = 16.4%) of daily food kilocalorie from HPF. Most younger infants (68%) and older infants (88%) had repeated exposure to the same HPF across the measurement period. Conclusions: The prevalence of HPF among baby foods in the U.S. is low. However, almost all infants were exposed to HPF, and HPF comprised a substantial percentage of daily food kilocalorie in infants' diets. Findings highlight the transition to solid food consumption during complimentary feeding period is a critical time for early HPF exposure.